Preparation process of nitrogen-doped carbon nanotube-based electrode material and efficient conversion application of biomass alcohols of nitrogen-doped carbon nanotube-based electrode material

The nitrogen-doped aminated multi-walled carbon nanotube electrode material prepared by grinding and programmed temperature annealing processes solves the environmental pollution and high cost problems of traditional selective oxidation of alcohols technology, and realizes efficient and stable oxidation of biomass alcohols, which is suitable for large-scale production.

CN121675004APending Publication Date: 2026-03-17SUN YAT SEN UNIVERSITY SHENZHEN +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511935621.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

In existing technologies, traditional selective oxidation of alcohols suffers from problems such as uncontrollable reactions, severe side reactions, serious environmental pollution, non-recoverable catalysts, and high costs. Furthermore, commercial nitrogen-doped carbon nanotube preparation processes are expensive, complex, and have low doping efficiency, making them unsuitable for large-scale, low-cost production.

Method used

A non-metal-guided green synthesis method was adopted to prepare nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) through grinding and programmed temperature annealing processes. This method achieves surface functionalization and nitrogen doping without the need for metal catalysts, and electrode materials were prepared by combining the method with spraying technology.

Benefits of technology

The prepared N-NH2-CNTs material exhibits excellent catalytic activity and stability in alkaline electrolytes, with low reaction initiation potential and high oxidation current density. It is suitable for the oxidation of various biomass alcohols, and is low in cost, environmentally friendly, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121675004A_ABST
    Figure CN121675004A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical new energy conversion, and particularly relates to a preparation process of a nitrogen-doped carbon nanotube-based electrode material and high-efficiency conversion application of biomass alcohols of the nitrogen-doped carbon nanotube-based electrode material. The nitrogen doping controllable adjustment of NH2-CNT is realized by adopting a grinding and program temperature control annealing process, then the dispersion liquid is prepared, the dispersion liquid is loaded on carbon paper in a spraying and infrared lamp irradiation drying manner to prepare the electrode, and the electrode is applied to an electro-catalysis biomass alcohol oxidation system for the first time. The nitrogen-doped aminated multi-walled carbon nanotubes can realize excellent catalytic activity and biomass alcohol oxidation capacity, which are higher than those of commercial platinum-carbon and nitrogen-doped CNTs materials. The initial potential of the reaction is as low as 1.1 V vs.RHE, and the oxidation current can reach 80 mA / cm < 2 > under the potential of 1.6 V vs.RHE. The preparation process is simple, the production cost is low, industrial large-scale production is easy, and the method has wide application prospects in the fields of energy, environmental protection, electro-catalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical new energy conversion technology, specifically relating to a preparation process of nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. Background Technology

[0002] With the increasing severity of the energy crisis and environmental pollution, the development of green, efficient, and sustainable chemical conversion technologies has become a core research direction in the fields of energy and materials science. Particularly in fine chemicals and biomass resource utilization, there is an urgent need to transform traditional high-energy-consuming and high-polluting processes towards environmentally friendly and economically efficient ones. Against this backdrop, the electrocatalytic oxidation of biomass-derived alcohols (EOBA) has become a hot topic in the interdisciplinary research of green chemistry and sustainable energy conversion because it can efficiently convert renewable carbon sources into high-value-added oxygen-containing compounds (such as aldehydes, ketones, acids, and esters), accompanied by anodic hydrogen production or cathodic reduction reactions (such as CO2 reduction or hydrogen evolution).

[0003] Traditional selective oxidation of alcohols mainly relies on homogeneous catalytic systems constructed from oxidants (such as dichromates, permanganates, or hydrogen peroxide) and transition metal salts (such as Ru, Pd, Co, etc.). Although these systems exhibit high catalytic activity, they suffer from the following significant drawbacks: (1) the reaction process is uncontrollable, with severe side reactions, making it difficult to achieve high selective conversion; (2) the systems are mostly acidic or strongly oxidizing environments, easily generating corrosive and toxic byproducts, resulting in a heavy environmental burden; and (3) the catalysts are not recyclable, have high costs, poor reusability, and are difficult to process. Therefore, constructing efficient, environmentally friendly, stable, and durable electrocatalytic solid-phase systems has become a research frontier in alcohol oxidation technology. In recent years, carbon-based materials have gradually become ideal carriers for constructing non-noble metal electrocatalysts due to their excellent conductivity, large specific surface area, strong structural tunability, and high environmental stability. In particular, carbon nanotubes (CNTs), as a type of carbon material with a one-dimensional cavity structure, not only possess high electron mobility and mechanical strength but can also be functionalized through various means, showing broad application prospects in electrochemical reactions. However, pure carbon nanotubes exhibit low activity in practical electrocatalytic reactions, and the catalytic process is often limited by the lack of effective active sites. To improve catalytic performance, heteroatom doping, especially nitrogen (N) doping, has become an important means to enhance its electronic structure regulation ability and catalytic activity.

[0004] Nitrogen doping can introduce functional groups such as pyridine nitrogen, graphitic nitrogen, and amino groups, leading to a redistribution of local charges on carbon nanotubes and enhancing their interaction with reaction substrates or intermediate states (such as free radicals or cations). This effectively improves electron transfer pathways and lowers reaction energy barriers. Furthermore, the introduction of amino or hydroxyl functional groups can significantly enhance the selective oxidation of alcohol molecules by strengthening hydrogen bonding and nucleophilic-electrophilic modulation capabilities. Previous studies have shown that during alcohol oxidation, oxygen-containing groups on the surface of carbon materials may reduce overall reactivity due to adsorption of byproducts or the formation of inert sites. However, nitrogen doping and surface amino functionalization can significantly improve catalytic selectivity and conversion efficiency while maintaining structural stability. Currently, commercially available nitrogen-doped carbon nanotubes are mainly achieved through chemical vapor deposition (CVD). This method typically uses ammonia, pyridine, or other nitrogen sources at high temperatures, and induces carbon nanotube growth through metal catalysts such as Fe and Co, while simultaneously completing nitrogen doping. Although CNTs prepared by CVD process have good performance in terms of structural uniformity and crystallinity, the method has the following shortcomings: (1) The preparation equipment is expensive, the process is complicated, and the reaction conditions are harsh, making it difficult to adapt to large-scale low-cost production; (2) Uneven distribution of gas source easily leads to low nitrogen doping efficiency and poor uniformity, affecting the stability and repeatability of the material; (3) Metal catalysts are required to induce carbon nanotube formation, and post-processing steps such as acid washing may introduce impurities or damage the microstructure of carbon nanotubes, thereby reducing the overall performance of the material.

[0005] To address the aforementioned issues, there is an urgent need to develop a green, low-cost, and metal-template-free process for preparing nitrogen-doped carbon nanotubes, which can achieve controllable functionalization modification and improve their electrocatalytic performance while ensuring structural integrity and doping efficiency. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, this invention provides a preparation process for nitrogen-doped carbon nanotube-based electrode materials and their application in the efficient conversion of biomass alcohols. The process of this invention does not rely on metal catalysts, has mild reaction conditions, and a simple operation procedure, making it suitable for large-scale applications. The prepared nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS), showing that they possess a highly ordered tubular structure, uniform nitrogen doping, abundant surface functional groups, low impurity content, and good structural integrity. The electrocatalytic performance of the N-NH2-CNTs material in the oxidation reactions of various biomass alcohols (such as benzyl alcohol, glycerol, and ethanol) was systematically tested in a typical three-electrode system. The results show that the material exhibits excellent onset potential (down to 1.1 V vs. RHE) and high oxidation current density (up to 80 mA / cm² at 1.6 V vs. RHE) in alkaline electrolytes. 2The N-NH2-CNTs exhibit excellent resistance to methanol cross-interference and long-term stability, with overall catalytic activity significantly superior to commercial Pt / C catalysts and conventional nitrogen-doped CNT materials. This indicates that N-NH2-CNTs possess great potential as a non-precious metal electrocatalyst alternative in alcohol oxidation reactions.

[0007] Based on the concept of non-metal-oriented green synthesis, this invention constructs a high-efficiency, stable, and low-cost carbon-based electrocatalytic material through nitrogen doping and synergistic amino functionalization. It provides a sustainable solution for the selective electrocatalytic oxidation of biomass-derived alcohols and has significant research value and broad practical application prospects.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a process for preparing nitrogen-doped carbon nanotube-based electrode materials, the preparation method comprising the following steps: (1) Aminated multi-walled carbon nanotubes (NH2-CNT) were mixed with a nitrogen source and then ground to obtain the ground powder; This invention uses carbon paper as the current collector substrate and NH2-CNT as the precursor. The surface functionalization treatment is achieved through grinding to adjust its surface chemical state. (2) After the powder is ground, it is annealed under nitrogen protection to obtain nitrogen-doped aminated multi-walled carbon nanotube powder, which is the nitrogen-doped carbon nanotube-based electrode material.

[0009] By adjusting the temperature gradient and holding time, the depth of surface nitrogen doping and the retention of functional groups can be controlled, thereby obtaining nitrogen-doped CNT materials with high structural stability and high active site density, namely N-NH2-CNTs.

[0010] Furthermore, in step (1), the aminated multi-walled carbon nanotubes have a purity >95%, a length of 40-60 μm, and a diameter of 8-15 nm.

[0011] Further, in step (1), the amino content of the aminated multi-walled carbon nanotubes is 0.7 mmol / g.

[0012] Furthermore, in step (1), the nitrogen source is urea.

[0013] Furthermore, in step (1), the mass of the nitrogen source is 1-20 times the total mass of the precursor.

[0014] Furthermore, the grinding time is ≥40 min.

[0015] Further, in step (2), the annealing temperature is 500-1000℃, the annealing time is 1-6 hours, and the heating rate and cooling rate are both 5°C / min.

[0016] A second aspect of this invention provides the application of the nitrogen-doped carbon nanotube-based electrode material prepared by the above-mentioned preparation process in the efficient conversion of biomass alcohols, wherein the method of application is as follows: Step S1: Nitrogen-doped aminated multi-walled carbon nanotube powder is dispersed in a mixture of isopropanol and Nafion solution, ultrasonically treated, and then sprayed onto hydrophilic carbon paper under the assistance of infrared lamp irradiation. Annealed N-NH2-CNTs materials were ultrasonically dispersed in a water-alcohol mixture to prepare a stable dispersion. The dispersion was then uniformly sprayed onto the surface of carbon paper using a spray gun, and simultaneously dried at low temperature with an infrared lamp to accelerate solvent evaporation and load uniformity, thereby preparing a directly usable composite electrode. Step S2: Using carbon paper loaded with nitrogen-doped aminated multi-walled carbon nanotubes as the working electrode, assemble a three-electrode electrolysis system, use alkaline electrolyte as the reaction medium, add biomass alcohol substrate, apply constant potential or linear scanning potential at room temperature, and achieve selective oxidation conversion of alcohol by electrochemical method.

[0017] Further, in step S1, the ratio of nitrogen-doped aminated multi-walled carbon nanotube powder to isopropanol is 4-6 mg / mL, and the volume ratio of isopropanol to Nafion solution is 100:3.

[0018] Furthermore, the solvent of the Nafion solution is ethanol, and the concentration of the Nafion solution is 5 wt%.

[0019] Furthermore, in step S1, the ultrasound duration is 30 minutes.

[0020] Further, in step S2, the alkaline solute in the alkaline electrolyte is NaOH or KOH, and the concentration of the alkaline solute is 0.1-2 mol / L.

[0021] Further, in step S2, the biomass alcohol substrate is at least one of aromatic alcohols, fatty alcohols, and polyols, and the concentration of the biomass alcohol substrate is 0.1-1 mol / L.

[0022] Furthermore, in step S2, the counter electrode of the three-electrode electrolysis system is a Pt counter electrode, and the reference electrode of the three-electrode electrolysis system is an Hg / HgO electrode or an Ag / AgCl electrode.

[0023] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a preparation process for nitrogen-doped carbon nanotube-based electrode materials and their application in the efficient conversion of biomass alcohols. Taking the benzyl alcohol oxidation process as an example, the inventors discovered that nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) catalytic materials achieve excellent catalytic activity and biomass alcohol oxidation capacity, exceeding that of commercial platinum-carbon and nitrogen-doped CNTs materials. The pyridine nitrogen active sites formed after urea doping synergistically interact with the -NH2 groups, promoting electron transfer between the biomass alcohol substrate and the electrode during the reaction. The reaction initiation potential can be reduced to 1.1 V vs. RHE, and the oxidation current can reach 80 mA / cm at a potential of 1.6 V vs. RHE. 2 Furthermore, it achieved a product production Faraday efficiency of up to 100% (up to 90%). It exhibits excellent resistance to methanol cross-interference and long-term electrochemical stability, making it suitable for practical operating environments. In addition, the preparation process is simple, safe, environmentally friendly, and pollution-free, with low equipment requirements. The raw materials are commercially available, resulting in low production costs and ease of industrialization and large-scale production. It has broad application prospects in energy, environmental protection, and electrocatalysis.

[0024] Specifically, the present invention has the following advantages: (1) The process of this invention is simple and does not require templates or metal catalysts: by combining grinding and programmed temperature-controlled annealing with functionalization treatment, there is no need to use high-temperature CVD equipment or precious metal auxiliary doping, which reduces costs and technical thresholds and avoids the structural damage caused by metal impurities and acid washing process in traditional processes.

[0025] (2) The present invention has precise doping and functional group control: By adjusting the type of precursor and heat treatment parameters in combination with the grinding process, the nitrogen content, doping morphology (pyridine nitrogen) and surface amino groups can be effectively controlled, providing a new path for controlling electrocatalytic performance.

[0026] (3) The present invention has excellent electrocatalytic performance: the first experiment confirmed the potential of N-NH2-CNTs material in the electrocatalytic application of biomass alcohol oxidation. Its comprehensive performance surpasses that of traditional commercial catalysts. It has high reaction activity, large current response and strong stability, and is the best among current non-precious metal catalytic materials.

[0027] (4) The present invention is applicable to a variety of alcohol substrates: the nitrogen-doped carbon nanotube-based electrode material exhibits good catalytic response to a variety of representative biomass alcohols such as aromatic alcohols, fatty alcohols, and polyols, indicating that it has a wide range of applications and good potential for platform development. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the preparation process of nitrogen-doped carbon nanotube-based electrode material in Example 1 and its application in the efficient conversion of biomass alcohols; Figure 2 Comparison of scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the N-NH2-CNT electrode material prepared in Example 1 of this invention and other typical carbon materials; wherein, a, b, and c are SEM images of multi-walled carbon nanotubes (CNTs), aminated multi-walled carbon nanotubes (NH2-CNTs), and nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping amount of 0.6 wt%, respectively. Figure 3 The images are TEM images of different electrode materials, where af represents TEM images of multi-walled carbon nanotubes (CNTs), aminated multi-walled carbon nanotubes (NH2-CNTs), nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with nitrogen doping of 0.2 wt%, nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with nitrogen doping of 0.4 wt%, nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with nitrogen doping of 0.6 wt%, and nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with nitrogen doping of 0.8 wt%. Figure 4 The images show TEM images and EDS-mapping spectra of different electrode materials. Specifically, ab represents the TEM image and EDS-mapping spectra of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt%, respectively; cd represents the TEM image and EDS-mapping spectra of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.8 wt%, respectively. Figure 5 The results of elemental analysis of the N-NH2-CNT electrode material prepared in this invention at different nitrogen doping levels are shown. Figure 6 X-ray diffraction (XRD) patterns of nitrogen-doped aminated multi-walled carbon nanotube (N-NH2-CNT) electrode materials with different nitrogen doping levels prepared in this invention and other carbon materials; Figure 7 The X-ray photoelectron spectroscopy (XPS) spectra of electrode materials prepared with different nitrogen doping levels according to the present invention are shown, where ad is the N 1s X-ray photoelectron spectroscopy (XPS spectrum) of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNT) with different nitrogen doping levels, and eh is the N 1s X-ray photoelectron spectroscopy (XPS spectrum) of nitrogen-doped multi-walled carbon nanotubes (N-CNT) with different nitrogen doping levels. Figure 8This invention compares the electrochemical oxidation activity of benzyl alcohol in electrode materials prepared with different N doping levels, where a is a comparison of the electrochemical oxidation activity of benzyl alcohol in nitrogen-doped multi-walled carbon nanotubes (N-CNTs) with different nitrogen doping levels, and b is a comparison of the electrochemical oxidation activity of benzyl alcohol in nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with different nitrogen doping levels. Figure 9 The comparison of the activity of electrode materials prepared by different nitrogen doping processes in the electrochemical oxidation of benzyl alcohol is shown in (a), and the comparison of the electrochemical oxidation activity of N-NH2-CNT material with nitrogen doping of 0.6 wt% on typical biomass alcohol substrates is shown in (b). Figure 10 The X-ray photoelectron spectroscopy (XPS) of the electrode materials with different nitrogen doping sites in this invention; Figure 11 Comparison of the electrochemical oxidation activity of benzyl alcohol in electrode materials prepared with different nitrogen doping sites according to the present invention; Figure 12 Comparison of electrochemical impedance spectroscopy (EIS) of the N-NH2-CNT electrode material prepared in Example 1 of the present invention under different benzyl alcohol substrate concentrations (a) and under different reaction potentials (b). Detailed Implementation

[0029] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all commercially available. The multi-walled carbon nanotubes mentioned in the embodiments and comparative examples of this invention are from Xianfeng Nano; the aminated multi-walled carbon nanotubes are from Xianfeng Nano; the urea is from Aladdin with a purity ≥99.5%; and the hydrophilic carbon paper is from Toray Industries, Japan.

[0031] Example 1: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. A method for doping N-active sites in multi-walled carbon nanotubes using a heat treatment process involving grinding and programmed temperature-controlled annealing was applied to an electrochemical biomass alcohol oxidation conversion reaction. The flowchart is shown below. Figure 1 As shown, the specific steps are as follows: (1) Commercially available multi-walled carbon nanotubes (CNTs) and aminated multi-walled carbon nanotubes (NH2-CNTs) were used as structural units as precursor powders for the preparation of catalytic materials. An appropriate amount of multi-walled carbon nanotubes (CNTs) or aminated multi-walled carbon nanotubes (NH2-CNTs) were taken as precursor powders and thoroughly mixed with 10 times the mass of urea (i.e., the mass ratio of carbon nanotubes to urea was 1:10, i.e., the nitrogen doping amount was 0.6wt%). The two were ground in a mortar for 40 minutes to facilitate the uniformity of the atmosphere and the control of the nitrogen doping effect during the subsequent pyrolysis process.

[0032] (2) The ground powder was evenly spread in a quartz sintering boat with a stable flow design and placed in a high-temperature tube furnace for high-temperature pyrolysis under the protection of high-purity nitrogen gas flow. Before annealing, a full vacuum was purged to eliminate residual oxygen. The heating and cooling rates of the tube furnace were both set to 5 ℃ / min. The annealing temperature was controlled at 600 ℃ and the holding time was usually 2 hours (120 minutes). Nitrogen-doped multi-walled carbon nanotubes N-CNT with a nitrogen doping amount of 0.6wt% and nitrogen-doped aminated multi-walled carbon nanotubes N-NH2-CNT with a nitrogen doping amount of 0.6wt% were obtained, respectively.

[0033] Scanning and transmission electron microscopy images of the N-NH2-CNT electrode material and other typical carbon materials prepared in this embodiment are, for example, Figure 2 As shown in the figure, a, b, and c are SEM images of multi-walled carbon nanotubes (CNTs), aminated multi-walled carbon nanotubes (NH2-CNTs), and nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen content of 0.6 wt% in this embodiment, respectively. It can be seen that the morphology of multi-walled carbon nanotubes (CNTs) and aminated multi-walled carbon nanotubes (NH2-CNTs) is quite similar, while the nanowires of 0.6 wt% nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) are more blurred.

[0034] (3) Take 5 mg of the annealed powder material and disperse it in a mixture of 1 ml isopropanol and 30 μL Nafion solution (5 wt%). After ultrasonic treatment for 30 minutes, spray the homogeneous catalyst suspension onto hydrophilic carbon paper under the auxiliary irradiation of infrared lamp.

[0035] (4) Carbon paper loaded with N-CNT or N-NH2-CNTs catalyst material was used as the working electrode, Pt as the counter electrode, and Hg / HgO as the reference electrode. The three electrodes were placed in a three-electrode electrolysis cell system. 1 M KOH aqueous solution was used as the supporting electrolyte, and 0.5 M benzyl alcohol was added. The performance was evaluated using an electrochemical workstation.

[0036] The electrochemical impedance spectroscopy (EIS) spectra of the N-NH2-CNT electrode material prepared in this embodiment are compared (a) under different benzyl alcohol substrate concentrations and (b) under different reaction potentials. Figure 12 As shown, it can be seen that the higher the substrate concentration of benzyl alcohol, the smaller the impedance value; the larger the reaction potential, the smaller the impedance value.

[0037] Example 2: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in embodiment 1. The difference between this embodiment and embodiment 1 is that the mass of urea added in step (1) is 0.1 times that of the precursor powder, and the nitrogen doping amount is 0.2 wt%.

[0038] Example 3: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass of urea added in step (1) is 1 times that of the precursor powder, and the nitrogen doping amount is 0.4 wt%.

[0039] Example 4: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in Embodiment 1. The difference between this embodiment and Embodiment 1 is that the mass of urea added in step (1) is 20 times that of the precursor powder, and the nitrogen doping amount is 0.8 wt%.

[0040] TEM images of different electrode materials, such as Figure 3 As shown, af represents TEM images of multi-walled carbon nanotubes (CNTs), aminated multi-walled carbon nanotubes (NH2-CNTs), nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with nitrogen doping of 0.2 wt%, 0.4 wt%, 0.6 wt%, and 0.8 wt%, respectively. It can be seen that with increasing nitrogen doping content, the lattice fringes of the carbon nanotube walls gradually become blurred, and the degree of defect increases.

[0041] TEM images and EDS-mapping spectra of different electrode materials, such as Figure 4As shown, ab represents the TEM images and EDS-mapping spectra of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt%, respectively; cd represents the TEM images and EDS-mapping spectra of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.8 wt%, respectively. It can be seen that nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.8 wt% have more obvious defects and more nitrogen distribution sites (green bright spots) compared to nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt%.

[0042] The elemental analysis results of the N-NH2-CNT electrode material prepared in this invention at different nitrogen doping levels are as follows: Figure 5 As shown, the nitrogen doping level increases linearly, with doping amounts of 0.22 wt%, 0.37 wt%, 0.60 wt%, and 0.78 wt%, respectively.

[0043] The X-ray diffraction (XRD) patterns of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) electrode materials with different nitrogen doping levels prepared in this invention, along with other carbon materials (multi-walled carbon nanotubes CNTs and aminated multi-walled carbon nanotubes NH2-CNTs), are shown below. Figure 6 As shown, it can be seen that as the nitrogen content increases, the orderliness of carbon nanotubes is gradually lost, which is consistent with the defect evolution law observed in the microscopic characterization.

[0044] The X-ray photoelectron spectroscopy (XPS) of electrode materials prepared with different nitrogen doping levels according to the present invention is as follows: Figure 7 As shown, ad represents the N 1s X-ray photoelectron spectra (XPS spectra) of nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNT) with different nitrogen doping amounts, and eh represents the N 1s X-ray photoelectron spectra (XPS spectra) of nitrogen-doped multi-walled carbon nanotubes (N-CNT) with different nitrogen doping amounts. It can be seen that within the nitrogen content range of 0.2–0.8 wt.%, the ratio of amino nitrogen to pyridine nitrogen remains at approximately 1:1; while the materials derived from aminated carbon nanotubes (NH2CNT) exhibit a stable 2:1 ratio of amino nitrogen to pyridine nitrogen.

[0045] The electrochemical oxidation activity of benzyl alcohol in electrode materials prepared with different N doping levels in this invention is compared as follows: Figure 8As shown, a compares the electrochemical oxidation activities of benzyl alcohol by nitrogen-doped multi-walled carbon nanotubes (N-CNTs) with different nitrogen doping amounts, and b compares the electrochemical oxidation activities of benzyl alcohol by nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with different nitrogen doping amounts. It can be seen that as the nitrogen content gradually increases, N-CNTs and N-NH2-CNTs with a nitrogen doping amount of 0.6 wt.% reach the maximum catalytic activity for benzyl alcohol electrochemical oxidation. With further increases in nitrogen content, the electrochemical catalytic activity of benzyl alcohol remains basically stable.

[0046] Figure 10 The X-ray photoelectron spectroscopy (XPS) of the electrode materials with different nitrogen doping sites in this invention (nitrogen-doped aminated multi-walled carbon nanotubes N-NH2-CNT with nitrogen doping of 0.6 wt%, nitrogen-doped multi-walled carbon nanotubes N-CNT with nitrogen doping of 0.6 wt%, and NCNT with nitrogen doping of 0.6 wt% (samples with an amino nitrogen / pyridine nitrogen ratio of 1:2) shows that the amino nitrogen / pyridine nitrogen ratios are 2:1, 1:1, and 1:2, respectively.

[0047] The electrochemical oxidation activity of benzyl alcohol of electrode materials prepared with different nitrogen doping sites in this invention (multi-walled carbon nanotubes (CNTs), aminated multi-walled carbon nanotubes (NH2-CNTs), nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt%, nitrogen-doped multi-walled carbon nanotubes (N-CNTs) with a nitrogen doping content of 0.6 wt%, and NCNTs with a nitrogen doping content of 0.6 wt% (sample with an amino nitrogen / pyridine nitrogen ratio of 1:2) is compared as follows: Figure 11 As shown, the sample with an amino nitrogen / pyridine nitrogen ratio of 2:1 exhibits the best electrochemical oxidation activity of benzyl alcohol.

[0048] Example 5: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment is the same as that in embodiment 1. The difference between this embodiment and embodiment 1 is that the high-temperature pyrolysis temperature in step (2) is selected as 500℃ for the experiment.

[0049] Example 6: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in embodiment 1. The difference between this embodiment and embodiment 1 is that the high-temperature pyrolysis temperature in step (2) is selected as 700℃ for the experiment.

[0050] Example 7: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment is the same as that in embodiment 1. The difference between this embodiment and embodiment 1 is that the high-temperature pyrolysis temperature in step (2) is selected as 800℃ for the experiment.

[0051] Example 8: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in embodiment 1. The difference between this embodiment and embodiment 1 is that the high-temperature stable pyrolysis time in step (2) is selected as 1 h for the experiment.

[0052] Example 9: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment is the same as that in embodiment 1. The difference between this embodiment and embodiment 1 is that the high-temperature stable pyrolysis time in step (2) is selected as 3 h for the experiment.

[0053] Example 10: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in Example 1. The difference between Example 1 and Example 1 is that in step (3), the powder material and the isopropanol and Nafion solution are selected as follows: 4 mg of powder material is dispersed in a mixture of 1 ml isopropanol and 30 μl Nafion solution (5 wt%).

[0054] Example 11: A preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols. The method in this embodiment refers to that in Example 1. The difference between Example 1 and Example 1 is that in step (3), the powder material and the isopropanol and Nafion solution are selected as follows: 6 mg of powder material is dispersed in a mixture of 1 ml isopropanol and 30 μl Nafion solution (5 wt%).

[0055] Example 12: Preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols The method in this embodiment is the same as that in Example 1. The difference between Example 1 and Example 1 is that benzyl methanol is used as the alcohol substrate in the electrochemical reaction cell in step (3).

[0056] Example 13: Preparation process of a nitrogen-doped carbon nanotube-based electrode material and its application in the efficient conversion of biomass alcohols The method in this embodiment is the same as that in Example 1. The difference between Example 1 and Example 1 is that glycerol is used as the alcohol substrate in the electrochemical reaction cell in step (3).

[0057] Figure 9The following is a comparison of the activity of electrode materials prepared by different nitrogen doping processes in the electrochemical oxidation of benzyl alcohol (a), including multi-walled carbon nanotubes (CNTs), CNNTs, aminated multi-walled carbon nanotubes, NH2-CNT-annealing (annealing temperature of 600 °C, holding time of 2 hours, heating rate and cooling rate of 5 °C / min), and nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt% for typical biomass alcohol substrates. It can be seen that nitrogen-doped aminated multi-walled carbon nanotubes (N-NH2-CNTs) with a nitrogen doping content of 0.6 wt% exhibit the best activity in the electrochemical oxidation of benzyl alcohol and also have relatively excellent electrochemical oxidation activity for typical biomass alcohol substrates.

[0058] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A process for preparing a nitrogen-doped carbon nanotube-based electrode material, characterized by, The preparation method comprises the following steps: (1) grinding amino-functionalized multi-walled carbon nanotubes as a precursor after mixing with a nitrogen source to obtain a ground powder; (2) spreading the ground powder and performing programmed temperature annealing under nitrogen protection to obtain nitrogen-doped amino-functionalized multi-walled carbon nanotube powder, i.e. a nitrogen-doped carbon nanotube-based electrode material.

2. The process for preparing a nitrogen-doped carbon nanotube-based electrode material according to claim 1, characterized by, In step (1), the purity of the amino-functionalized multi-walled carbon nanotubes is > 95%, the length is 40-60 μm, and the diameter is 8-15 nm.

3. The process for preparing a nitrogen-doped carbon nanotube-based electrode material according to claim 1, characterized by, In step (1), the amino-functionalized multi-walled carbon nanotubes have an amino content of 0.7 mmol / g.

4. The process for preparing a nitrogen-doped carbon nanotube-based electrode material according to claim 1, characterized by, In step (1), the nitrogen source is urea.

5. The process for preparing a nitrogen-doped carbon nanotube-based electrode material according to claim 1, characterized by, In step (1), the mass of the nitrogen source is 1-20 times the total mass of the precursor.

6. The process for preparing a nitrogen-doped carbon nanotube-based electrode material according to claim 1, wherein In step (2), the annealing temperature is 500-1000 ℃, the annealing time is 1-6 hours, and the heating rate and the cooling rate are both 5 ℃ / min.

7. The use of the nitrogen-doped carbon nanotube-based electrode material prepared by the preparation process according to any one of claims 1-6 in the efficient conversion of biomass alcohol, characterized in that, The application method is: Step S1: dispersing the nitrogen-doped amino-functionalized multi-walled carbon nanotube powder in a mixture of isopropanol and a Nafion solution, ultrasonic treatment, and then spraying onto a hydrophilic carbon paper under the auxiliary irradiation of an infrared lamp; Step S2: using the carbon paper loaded with the nitrogen-doped amino-functionalized multi-walled carbon nanotubes as a working electrode, assembling a three-electrode electrolytic system, using an alkaline electrolyte as a reaction medium, adding a biomass alcohol substrate, applying a constant potential or a linear scanning potential under room temperature conditions, and realizing selective oxidation conversion of the alcohol by an electrochemical method.

8. The use of the nitrogen-doped carbon nanotube-based electrode material according to claim 7 in the efficient conversion of biomass alcohol, characterized in that, In step S1, the use amount ratio of the nitrogen-doped amino-functionalized multi-walled carbon nanotube powder to isopropanol is 4-6 mg / mL, and the volume ratio of isopropanol to the Nafion solution is 100:

3.

9. The use of the nitrogen-doped carbon nanotube-based electrode material according to claim 7 in the efficient conversion of biomass alcohol, characterized in that, In step S2, the alkaline solute in the alkaline electrolyte is NaOH or KOH, and the concentration of the alkaline solute is 0.1-2 mol / L.

10. The use of the nitrogen-doped carbon nanotube-based electrode material according to claim 7 in the efficient conversion of biomass alcohol, characterized in that, In step S2, the biomass alcohol substrate is at least one of an aromatic alcohol, a fatty alcohol, and a polyhydric alcohol, and the concentration of the biomass alcohol substrate is 0.1-1 mol / L.